Enzymes - important players in green chemistry - Tarczykowska, Agata; Kochański, Bartosz; Kałużny, Krystian; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Green chemistry has become a worldwide approach that leads to sustainable growth through application and development of its principles. A lot of work has to be put into designing new processes comprising of materials which do not emit pollutants to the atmosphere. Inventing new safer methods and finding less harmful products can be challenging. Enzymes are a great hope of scientists in the field of green chemistry. Enzymes as catalysts require mild conditions therefore it is a great way of saving resources such as energy or water. Processes with the use of enzymes have become more feasible by being more cost effective and eco friendly. Taking into account the benefits of green chemistry, enzyme biocatalysis has quickly replaced traditional chemical processes in several fields, and this substitution is going to reach even more areas because of new emerging technologies in enzyme engineering.